Nutritional Knowledge, Nutritional Status, Compliance with Iron Supplement Tablets, and the Incidence of Anemia in Female Adolescent - Nuraina, Viana Fauzia; Hidayani, Wuri Ratna (The Indonesian Institute of Science and Technology Research, 2024)
Anemia is a significant health issue in society, and it is prevalent, including in Indonesia. This condition can substantially impact the economy, health, and social well-being. This research aims to determine the relationship between nutritional knowledge, nutritional status, compliance with iron supplement tablet consumption, and the incidence of anemia in adolescent girls at Al-Ishlah Vocational School in the year 2023. This study aims to contribute to developing knowledge related to public health, especially in nutrition and anemia. The research adopts a quantitative approach with an analytical method and a cross-sectional design, using purposive sampling to select 47 female adolescents from a population of 143 students. Data analysis involves univariate and bivariate analyses conducted using the Statistical Program for Social Sciences (SPSS). The findings reveal no significant relationship between nutritional knowledge and the incidence of anemia in adolescent girls (p=0.654). Similarly, there is no significant correlation between nutritional status and the occurrence of anemia in these adolescents (p=0.442). Additionally, there is no significant relationship between compliance with iron supplement tablet consumption and the incidence of anemia in the same group of adolescent girls (p=1.000). Recommendations include collaborative efforts between schools and healthcare services to enhance adolescent nutrition, regular monitoring for anemia prevention, health departments implementing policies to enhance nutrition education in schools, school nutrition campaigns, educational activities, and institutions contributing to developing more effective strategies.